2023
DOI: 10.1186/s13256-023-04061-2
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery syndrome in an 8-year-old boy: a case report

Ayah Aldagher,
Rodaina Almasri,
Jaber Mahmoud

Abstract: Background Superior mesenteric artery syndrome (SMAS), also known as Wilkie's syndrome, is a rare disease that mainly presents as intestinal obstruction with a variable incidence ranging from 0.013 to 0.3% (Salehzadeh et al. in Case Rep Gastrointest Med, 2019, 10.1155/2019/3458601). In this syndrome, the third part of the duodenum, located between the abdominal aorta and the superior mesenteric artery, is wholly or partially obstructed (Mosalli et al. in J Pediatr Surg 46:e29–31, 2011). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We found that the age at diagnosis of superior mesenteric artery syndrome ranged from 6 to 12 years. 19 30 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the age at diagnosis of superior mesenteric artery syndrome ranged from 6 to 12 years. 19 30 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Various symptoms were recorded in the literature, such as abdominal pain and early satiety, but the most common symptom, which was detected in all these cases, was vomiting. 19 30 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation